Internet issues : blogging the digital divide and digital libraries - Evans, Cassie M. (Internet policies and issues, 2010)
A blog is a type of website, usually maintained by an individual with regular entries of commentary, descriptions of events, or other material such as graphics or video. The term digital divide refers to the gap between people with effective access to digital and information technology and those with very limited or no access at all. It includes the imbalances in physical access to technology as well as the imbalances in resources and skills needed to effectively participate as a digital citizen. A digital library is a library in which collections are stored in digital formats. This book provides insight into the technologies provided by the internet such as blogging, digital libraries and the digital divide, which both enhance communication between certain individuals and limit others.